P016: Low risk ankle rule, high reward-a quality improvement initiative to reduce ankle x-rays in the pediatric emergency department. (15th May 2017) - Al-Sani, F.; Ben-Yakov, M.; Harvey, G.; Gantz, J.; Jacobson, D.; Boutis, K.; Ostrow, O.; Principi, T.
Abstract : Introduction: Our tertiary care institution embarked on the Choosing Wisely campaign to reduce unnecessary testing, and selected the reduction of ankle x-rays as part of its top five priority initiatives. The Low Risk Ankle Rule (LRAR), an evidence-based decision rule, has been derived and validated to clinically evaluate ankle injuries which do not require radiography. The LRAR, is cost-effective, has 100% sensitivity for clinically important ankle injuries and reduces ankle imaging rates by 30-60% in both academic and community setting. Our objective was to significantly reduce the proportion of ankle x-rays ordered for acute ankle injuries presenting to our pediatric Emergency Department (ED).Methods: Medical records were reviewed for all patients presenting to our tertiary care pediatric ED (ages 3- 18 years) with an isolated acute ankle injury from Jan 1, 2016-Sept 30, 2016. Children with outside imaging, an injury that occurred >72 hours prior, or those who had a repeat ED visit for same injury were excluded. Quality improvement (QI) initiatives included multidisciplinary staff education about the LRAR, posters placed within the ED highlighting the LRAR, development of a new diagnostic imaging requisition for ankle x-rays requiring use of the LRAR and collaboration with the Division of Radiology to ensure compliance with new requisition. The proportion of patients presenting to the ED with acute ankle injuries who received x-rays was measured. ED length of stay (LOS), return visits to the ED and orthopedic referrals were collected as balancing measures.Results: At baseline 88% of patients with acute ankle injuries received x-rays. Following our multiple interventions, the proportion of x-rays decreased significantly to 54%, (p<0.001). This decrease in x-ray rate was not associated with an increase in ED LOS, ED return visits or orthopedic referrals. There was an increase uptake of the dedicated x-ray requisition over time to 71%.Conclusion: This QI initiative to increase uptake of the LRAR, resulted in a significant reduction of ankle x-rays rates for children presenting with acute ankle injuries in our pediatric ED without increasing LOS, return visits or need for orthopedic referrals for missed injuries. Just as in the derivation and validation studies, the reductions have been sustained and reduced unnecessary testing and ionizing radiation.